2018
DOI: 10.1177/0961203318768886
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of fracture risk in patients with systemic lupus erythematosus

Abstract: Objectives Bone loss in systemic lupus erythematosus is multifactorial. Recent studies demonstrate corticosteroids, previous fractures and increasing age decrease bone mineral density. The effect of body mass index and fat mass are less well characterized. We sought to determine fracture risk factors in patients undergoing dual-energy X-ray absorptiometry scanning at a district hospital in 2004-2015. Methods Standard dual-energy X-ray absorptiometry parameters were recorded, plus rheumatoid arthritis diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In one study, past or current smoking (vs never) was significantly associated with increased risk of organ damage (HR 1.7, 95% CI 1.1 to 2.6). 58 In other studies, smoking was associated with increased: risk of lung cancer 59 ; odds of thrombotic events 60 61 ; frequency, odds and risk of CV and cerebrovascular events 62–64 ; odds of fracture 65 ; odds of cutaneous damage and odds of early myocardial infarction. 66 Three studies did not find any association between smoking and the risk of myocardial infarction and/or stroke, 67 depression 68 and cutaneous features of active lupus, 69 respectively.…”
Section: Resultsmentioning
confidence: 87%
“…In one study, past or current smoking (vs never) was significantly associated with increased risk of organ damage (HR 1.7, 95% CI 1.1 to 2.6). 58 In other studies, smoking was associated with increased: risk of lung cancer 59 ; odds of thrombotic events 60 61 ; frequency, odds and risk of CV and cerebrovascular events 62–64 ; odds of fracture 65 ; odds of cutaneous damage and odds of early myocardial infarction. 66 Three studies did not find any association between smoking and the risk of myocardial infarction and/or stroke, 67 depression 68 and cutaneous features of active lupus, 69 respectively.…”
Section: Resultsmentioning
confidence: 87%
“…In view of the compromised quality of life resulting from SLE, patients who manifest musculoskeletal and body composition changes are dependent on the performance of routine activities and greater physical inactivity, greater perception of pain in muscles and joints, greater neurocognitive impairment, increased risk of fracture, increased risk of cardiovascular complications, metabolic syndrome and ovarian failure, further compromising quality of life [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Women with lupus may be nearly five times more likely to experience a fracture from poor bone quality, and fractures frequently occur in the femur, resulting in decreased quality of life and a mortality rate as high as nearly 25% in the first year after femur fracture. [9][10][11][12][13] The standard-of-care test used to assess bone quality is dual-energy x-ray absorptiometry (DXA) assessment of BMD; however, as a 2D planar technique, DXA does not assess all the changes in bone tissue that can occur in SLE and does not entirely capture fracture risk. Bone marrow is an important component of bone tissue, and biopsies have shown that bone marrow is one of the organ targets affected by immune mechanisms in active SLE.…”
mentioning
confidence: 99%
“…Recent studies have shown that SLE patients have higher fracture rates, even when controlling for BMD and other variables suggesting disease‐specific risk, which is independent of BMD 6–8 . Women with lupus may be nearly five times more likely to experience a fracture from poor bone quality, and fractures frequently occur in the femur, resulting in decreased quality of life and a mortality rate as high as nearly 25% in the first year after femur fracture 9–13 . The standard‐of‐care test used to assess bone quality is dual‐energy x‐ray absorptiometry (DXA) assessment of BMD; however, as a 2D planar technique, DXA does not assess all the changes in bone tissue that can occur in SLE and does not entirely capture fracture risk.…”
mentioning
confidence: 99%